The Effect of Learning Approach and Hand-Eye Coordination Level on Two-Point Jump Shot Accuracy: An Experimental Study in Basketball Course - Abady, Andi Nur; Siregar, Fajar Siddik; Syahruddin, Syahruddin; Helmi, Boby; Almunawar, Ahmad; bin Abdullah, Nagoor Meera (Journal of Innovation in Educational and Cultural Research, 2026)
Two-point shooting ability is an essential skill in basketball learning, but third-semester PJKR students still show differences in accuracy influenced by learning approaches and hand-eye coordination levels. This study aims to analyze the effects of learning approaches, hand-eye coordination, and their interaction on two-point shooting accuracy. The study used a quantitative method with a 2×2 factorial experimental design. The research subjects consisted of 32 third-semester PJKR students at STOK Bina Guna, who were grouped by learning approach (Technical Approach and Progressive Skill Practice) and hand-eye coordination level (high or low). Data were collected using eye-hand coordination tests and two-point shooting accuracy tests, and analyzed using a two-way ANOVA. The results showed that the learning approach and eye-hand coordination significantly affected two-point shooting accuracy, with Progressive Skill Practice yielding better results. There was also a significant interaction between the two variables, confirming that learning effectiveness depends on students' coordination abilities. This study contributes to the development of sports pedagogy by emphasizing the importance of adaptive, individual-characteristic-based shooting instruction in physical education.